Meningitis Associated with Simultaneous Infection by Multiple Dengue Virus Serotypes in Children, Brazil - Paula Eillanny Silva Marinho (Emerging Infectious Diseases, 2017)
To determine the causes of viral meningitis, we analyzed 22 cerebrospinal fluid samples collected during the 2014–2015 dengue epidemics in Brazil. We identified 3 serotypes of dengue virus (DENV-1, -2, and -3), as well as co-infection with 2 or 3 serotypes. We also detected the Asian II genotype of DENV-2.